2022
DOI: 10.1021/acs.analchem.2c02232
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Electrode Biosensors for N-Hydroxylated Prodrugs Incorporating the Mitochondrial Amidoxime Reducing Component

Abstract: Human mitochondrial amidoxime reducing component 1 and 2 (mARC1 and mARC2) were immobilised on glassy carbon electrodes using the crosslinker glutaraldehyde. Voltammetry was performed in the presence of the artificial electron transfer mediator methyl viologen, whose redox potential lies negative of the enzymes' Mo VI/V and Mo V/IV redox potentials which were determined from optical spectroelectrochemical and EPR measurements. Apparent Michaelis constants obtained from catalytic limiting currents at various su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The FMN and the Fe/S clusters all make significant contributions to the UV–vis spectrum while the Mo cofactor is a relatively weak chromophore and optical absorption changes are undetectable in the presence of redox-active Fe/S clusters, flavins, or hemes. In the less common situations where the Mo cofactor is the only redox active chromophore present (e.g., human mARC1 and mARC2, Haemophilus influenzae MtsZ, and E. coli YiiM), optical spectroelectrochemistry has been successful in measuring the Mo VI/V and Mo V/IV redox potentials at high protein concentrations. As will be discussed later, electron paramagnetic resonance (EPR) spectroscopy is much better suited to Mo redox potential measurement in enzymes where other cofactors are present.…”
Section: Resultsmentioning
confidence: 99%
“…The FMN and the Fe/S clusters all make significant contributions to the UV–vis spectrum while the Mo cofactor is a relatively weak chromophore and optical absorption changes are undetectable in the presence of redox-active Fe/S clusters, flavins, or hemes. In the less common situations where the Mo cofactor is the only redox active chromophore present (e.g., human mARC1 and mARC2, Haemophilus influenzae MtsZ, and E. coli YiiM), optical spectroelectrochemistry has been successful in measuring the Mo VI/V and Mo V/IV redox potentials at high protein concentrations. As will be discussed later, electron paramagnetic resonance (EPR) spectroscopy is much better suited to Mo redox potential measurement in enzymes where other cofactors are present.…”
Section: Resultsmentioning
confidence: 99%
“…The assay is not suitable for substances with fluorescence properties similar to those of NADH. For these, an HPLC-MS analysis as described by Ginsel et al or the voltammetry based assay as described by Zapiter et al would be more appropriate. , Both methods are useful for detecting novel substrates for the mARC enzyme system. Neither method is suitable for high throughput, but they are valuable methods for verifying turnover.…”
Section: Resultsmentioning
confidence: 99%
“…The enzymatic characterization by mARC was initially studied using a method described by Clement et al using time-consuming HPLC protocols for analysis of substrate and reduced product. , This method was further optimized by Kotthaus et al and Krompholz et al ,, An assay based on cyclic voltammetry with a mARC immobilized to an electrode surface was developed to be able to detect mARC catalyzed reduction without requiring the electron delivery component Cyb5R3 or even Cyb5B. , A significant improvement for screening and kinetic characterization was introduced by Indorf et al, establishing a UV–vis spectroscopic method for the determination of mARC activity . It was shown that reduction of N -oxygenated substrates by mARC enzymes can be monitored in real time through the decrease of NADH absorbance ( A 340 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports in the literature represent the applicability of this sensing format for detecting cancer cells. [288][289][290] Several review studies represent the significance of organelles and cell.…”
Section: Immunosensors For Other Biomarkersmentioning
confidence: 99%
“…Monitoring of redox activities of living cells via analysis of NADH released from mitochondria is of great interest in cell screening and cancer therapy. Numerous reports in the literature represent the applicability of this sensing format for detecting cancer cells 288–290 . Several review studies represent the significance of organelles and cell.…”
Section: Cytosensorsmentioning
confidence: 99%